ARcadia: A Rapid Prototyping Platform for Real-time Tangible Interfaces - Kelly, Annie; Shapiro, R. Benjamin; de Halleux, Peli; Ball, Thomas (Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
Paper-based fabrication techniques offer powerful opportunities to prototype new technological interfaces. Typically, paper-based interfaces are either static mockups or require integration with sensors to provide real-time interactivity. The latter can be challenging and expensive, requiring knowledge of electronics, programming, and sensing. But what if computer vision could be combined with prototyping domain-aware programming tools to support the rapid construction of interactive, paper-based tangible interfaces? We designed a toolkit called ARcadia that allows for rapid, low-cost prototyping of TUIs that only requires access to a webcam, a web browser, and paper. ARcadia brings paper prototypes to life through the use of marker based augmented reality (AR). Users create mappings between real-world tangible objects and different UI elements. After a crafting and programming phase, all subsequent interactions take place with the tangible objects. We evaluated ARcadia in a workshop with 120 teenage girls and found that tangible AR technologies can empower novice technology designers to rapidly construct and iterate on their ideas.